Improving Science Learning Outcomes Through Problem Based Learning Methods in Class IV SDN 176 Palembang - Wahyuni, Asri; Annisa Satia; Cythia Ingga Pratiwi; Clara Dara Mania; Desi Ulfa Sari (PT ARRUS Intelektual Indonesia, 2024)
This research discusses the use of Problem Based Learning (PBL) to improve student learning outcomes in learning science and technology regarding plant body parts in class IV.C at SDN 176 Palembang. The research was carried out using the classroom action research (PTK) method which includes two cycles, including planning, implementation, observation, and reflection. The research results show a significant increase in student learning completion after implementing PBL. Before the cycle, only 40% of students had completed the KKM, increasing to 64% in the first cycle and 88% in the second cycle. PBL has proven to be effective in increasing students' understanding and motivating them to think critically and creatively in solving problems related to science material.